Hubungan Sikap Perawat dengan Kinerja Perawat di Ruang Rawat Inap Kelas III Rumah Sakit Pertamina Bintang Amin Bandar Lampung - Yosi Adelta; M. Arifki Zainaro; Triyoso Triyoso (Universitas Malahayati Lampung, 2023)
ABSTRACT Performance is very important for research, good and bad nurse services in serving patients can be seen from their performance. Performance is the result or level of success of a person as a whole during a certain period to carry out a task compared to various possibilities, such as work standards, targets or targets or performance that has been determined in advance and has been mutually agreed upon. In addition to motivation, there are also other factors that can affect the performance of nurses, namely the attitude of nurses at work. Attitude is a positive or negative feeling and psychological state that is often prepared, studied, and regulated through experience, which has a specific influence on a person's response to people, situations, and objects. To know the relationship between attitudes of nurses with the performance of nurses in the Class III Inpatient Room at Pertamina Bintang Amin Hospital in 2022. This type of research uses quantitative, analytical survey research design with a cross sectional approach, the population and sample are nurses at Pertamina Bintang Hospital as many as 38 respondents, sampling technique using purposive sampling, data analysis using univariate and bivariate using chi square. Seen by 38 respondents, nurses who have a good attitude are 17 respondents (44.7%) with good nurse performance as many as 15 respondents (39.5%) and nurses' performance is not good as many as 2 respondents (5.3%), while the attitude of nurses is not good. 21 respondents (55.3%) poor nurses with good nurse performance as many as 4 respondents (10.5%) and poor nurse performance as many as 17 respondents (44.7%). Most of the nurses ' attitudes were in the poor category. The results of data analysis using the chi square test showed that the p-value had a relationship between the attitude of nurses and the performance of nurses in the class III inpatient room at Pertamina Bintang Amin Hospital in 2022. Keywords: Nurse Attitude, Nurse Performance ABSTRAK Kinerja sangat penting untuk dilakukan penelitian, baik buruk nya pelayanan perawat dalam melayani pasien dapat dilihat dari kinerjanya. Kinerja merupakan hasil atau tingkat keberhasilan seseorang secara keseluruhan selama periode tertentu untuk melaksanakan tugas dibandingkan dengan berbagai kemungkinan, seperti standar kerja , target atau sasaran atau kinerja yang telah ditentukan terlebih dahulu dan telah disepakati bersama . Selain motivasi terdapat juga faktor lain yang dapat mempengaruhi kinerja perawat, yaitu sikap perawat dalam bekerja. Sikap merupakan suatu perasaan positif atau negatif serta keadaan psikis yang sering disiapkan, dipelajari, dan diatur melalui pengalaman, yang memberikan pengaruh spesifik terhadap respon seseorang terhadap orang, situasi, dan objek. Diketahui hubungan sikap perawat dengan kinerja perawat di Ruang Rawat Inap Kelas III Rumah Sakit Pertamina Bintang Amin Tahun 2022. Jenis penelitian menggunakan kuantitatif, rancangan penelitian survey analitik dengan pendekatan cross sectional, Populasi dan sampel adalah perawat di Rumah Sakit Pertamina Bintang Amin sebanyak 38 responden, teknik sampling menggunakan purposive sampling, analisa data menggunakan univariat dan bivariat menggunakan chi square. Dilihat 38 responden, perawat yang memiliki sikap baik sebanyak 17 responden (44,7%) dengan kinerja perawat baik sebanyak 15 responden (39,5%) dan kinerja perawat kurang baik sebanyak 2 responden (5,3%), sedangkan sikap perawat kurang baik sebanyak 21 responden (55,3%) dengan kinerja perawat baik sebanyak 4 responden (10,5%) dan kinerja perawat kurang baik sebanyak 17 responden (44,7%) . Sebagian besar sikap perawat dengan kategori kurang baik. Hasil analisa data menggunakan uji chi square didapat nilai p-value ada hubungan sikap perawat dengan kinerja perawat di ruang rawat inap kelas III Rumah Sakit Pertamina Bintang Amin. Kata Kunci: Sikap Perawat, Kinerja Perawat